2011
DOI: 10.1074/jbc.m110.140202
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Role of Periostin in Postnatal Tooth Formation and Mineralization

Abstract: Periostin plays multiple functions during development. Our previous work showed a critical role of this disulfide-linked cell adhesion protein in maintenance of periodontium integrity in response to occlusal load. In this study, we attempted to address whether this mechanical response molecule played a direct role in postnatal tooth development. Our key findings are 1) periostin is expressed in preodontoblasts, and odontoblasts; and the periostin-null incisor displayed a massive increase in dentin formation af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
54
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(57 citation statements)
references
References 33 publications
(34 reference statements)
2
54
1
Order By: Relevance
“…In keeping with the findings of the PDL analysis in Mkx −/− mice, gene expression analysis in MKXsilencing and Mkx-overexpression experiments using hPDL fibroblasts revealed that MKX strongly and specifically promotes the expression of a set of extracellular matrix genes related to PDL tissue formation, including COL1A1 and COL1A2, which are similar to those reported in mesenchymal stem cells (Liu et al, 2015;Otabe et al, 2015). In particular, in PDL cells, Postn, which is among the extracellular matrix adhesion molecules mainly expressed in the bone, periosteum, and PDL tissues (KruzynskaFrejtag et al, 2004;Ma et al, 2011;Rios et al, 2005), was significantly decreased in the M1 PDL in 10-week-old Mkx −/− mice in vivo. In addition, Postn-deficient mice exhibit a phenotype of vertical PDL expansion and alveolar bone resorption in the M1 furcation area (Horiuchi et al, 1999;Rios et al, 2008), suggesting that PDL phenotype in Mkx −/− mice could, in part, be due to the suppression of Postn.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…In keeping with the findings of the PDL analysis in Mkx −/− mice, gene expression analysis in MKXsilencing and Mkx-overexpression experiments using hPDL fibroblasts revealed that MKX strongly and specifically promotes the expression of a set of extracellular matrix genes related to PDL tissue formation, including COL1A1 and COL1A2, which are similar to those reported in mesenchymal stem cells (Liu et al, 2015;Otabe et al, 2015). In particular, in PDL cells, Postn, which is among the extracellular matrix adhesion molecules mainly expressed in the bone, periosteum, and PDL tissues (KruzynskaFrejtag et al, 2004;Ma et al, 2011;Rios et al, 2005), was significantly decreased in the M1 PDL in 10-week-old Mkx −/− mice in vivo. In addition, Postn-deficient mice exhibit a phenotype of vertical PDL expansion and alveolar bone resorption in the M1 furcation area (Horiuchi et al, 1999;Rios et al, 2008), suggesting that PDL phenotype in Mkx −/− mice could, in part, be due to the suppression of Postn.…”
Section: Discussionsupporting
confidence: 65%
“…Although the PDL is composed of heterogeneous cell types such as fibroblasts, osteoblasts, osteoclasts, cementoblasts, endothelial cells, sensory cells and their progenitor or stem cells (Beertsen et al, 1997;Maeda et al, 2011;Ueda-Maeda, 2006), fibroblasts are responsible for the fibrous attachment of the PDL. The components of PDL include type I collagen (70-80%), other types of collagen (type III, IV, V, VI and XII collagens), and other extracellular matrix proteins such as periostin (Postn), glycoproteins and proteoglycans, all of which are mainly produced by PDL fibroblasts (Aukkarasongsup et al, 2013;Beertsen et al, 1997;Ma et al, 2011;Rios et al, 2005;Sloan, 1979;Ahuja, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Scx is also a member of the twist subfamily of basic helix-loophelix transcription factors (Atchley and Fitch, 1997). The inhibitory action of Pstn on mineralization was reported using an odontoblastic cell line (Ma et al, 2011). We found that not only Scx but also Pstn were significantly upregulated on the tensile force-loaded site of the PDL.…”
Section: Inhibitory Action Of Scx On Mineralization Of the Ecm Of Pdlmentioning
confidence: 59%
“…For a more detailed analysis, we compared the expression of periostin (Pstn; Postn -Mouse Genome Informatics), a major ECM component of the PDL (Ma et al, 2011), with the expression of Scx. In a maxillary second molar of a 6-week-old ScxGFP Tg mouse, Pstn was localized to the gingival lamina propria (red arrowheads in Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Periostin, initially identified as osteoblast-specific factor 2, secreted from osteoblasts (23), is specifically expressed in collagen-rich fibrous connective tissues such as PDL (21). Adult periostin null mice were shown to exhibit a periodontal disease phenotype including external root resorption caused by collagen fibril disorganization with defective fibronectin expression (17,22). Additionally, it has been reported that TGF-β can increase periostin expression in PDL (27).…”
mentioning
confidence: 99%